7(1 - q) = -3(5 + 3q)

7(1 - q) = -3(5 + 3q) ;
7 - 7q = -15 - 9q ;
-7q + 9q = -15 - 7 ;
2q = -22 ;
q = -22/2 ;
q = -11

Expert answered|Frankie17851|Points 1580|

Question

Asked 5/2/2012 10:59:33 AM

Updated 7/3/2018 9:47:20 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

-4(6-7x)=52 **Weegy:** Answer is x=3 **User:** 3x+4x-7=21 **Weegy:** Answer is x=4 **User:** 2x+9x-2=31 **Weegy:** Answer is x=3 **User:** -3n+9+5n=-17 **Weegy:** Answer is n= -13 **User:** 4x-5-7x=-14 **Weegy:** Answer is x=3 **User:** 3.8=0.5(8n-4.6) **Weegy:** Answer is n=1.525 **User:** 0.456=-0.3(7n-31.2) **Weegy:** Answer is n= -4.24 **User:** -34=-8b+16-6b **Weegy:** b= 3.57 **User:** 14.2=0.4(20n-7.8) **Weegy:** n = 2.165 **User:** -0.848=-0.2(6.5n-2) **Weegy:** Answer is n= 0.96 **User:** 8x-4=-7+5x **Weegy:** Answer is x = -1 **User:** 5(x+3)=-9+3x **Weegy:** Answer is x= -12 **User:** 8-8y=2y+78 **Weegy:** Answer is y = -7 **User:** 5x+17=3x+7 **Weegy:** Answer is x = -5 **User:** 5(y+7)=10y **Weegy:** Answer is y = 7 **User:** 4(2x+1)=3(x+8) **Weegy:** Answer is x = 4 **User:** 2(5m+4)=2(3m-10) **Weegy:** Answer is m = -7 **User:** 3y+7=y+13 **Weegy:** Answer is y = 3 **User:** 8(y-2)=4y **Weegy:** Answer is y = 4 (More)

Question

Expert Answered

Updated 6/19/2014 8:02:46 AM

1 Answer/Comment

37 + 8q = 65 + 7q

Question

Not Answered

Updated 12/29/2017 3:08:38 PM

1 Answer/Comment

37 + 8q = 65 + 7q

8q - 7q = 65 - 37

q = 28

8q - 7q = 65 - 37

q = 28

Added 12/29/2017 3:08:38 PM

This answer has been confirmed as correct and helpful.

3.2-0.08w=-4 **Weegy:** Answer is w= 90
SOLUTION
-0.08w=-4-3.2; -0.08w=-7.2; w=-7.2/0.08; w=90 **User:** -0.5(0.3x-0.6)=-1.5 **User:** 4x+9+7x=31 **Weegy:** 4x+9+7x=31,
11x+9=31,
11x=31-9,
11x=22,
x=22/11,
x=2
**User:** -4(6-7x)=52 **Weegy:** -4(6-7x)=52,
-24+28x=52,
28x=52+24,
28x=76,
x=76/28,
x=2.714
(More)

Question

Expert Answered

Updated 8/18/2014 1:28:41 PM

1 Answer/Comment

The answer for -0.5(0.3x-0.6)=-1.5 is x=12.

-0.5(0.3x-0.6)=-1.5

-0.5*0.3x+0.5*0.6=-1.5

-0.15x+0.3=-1.5

-0.15x=-1.5-0.3

-0.15x=-1.8

0.15x=1.8

x=1.8/0.15

x=12.

-0.5(0.3x-0.6)=-1.5

-0.5*0.3x+0.5*0.6=-1.5

-0.15x+0.3=-1.5

-0.15x=-1.5-0.3

-0.15x=-1.8

0.15x=1.8

x=1.8/0.15

x=12.

Added 8/18/2014 6:00:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/18/2014 1:28:44 PM], Rated good by andrewpallarca

33,673,385

questions answered

There are no comments.